#TITLE_ALTERNATIVE# - (NIM : 10206067); Pembimbing : Gunawan Handayani, MSCE, Ph.D, HAMZAH
DC resistivity method is one of the geophysical methods that can be used to determine earth subsurface conditions. This method is done by injecting direct currents to the surface of the earth and then measuring the generated potential difference, thus the apparent resistivity values can be obtained for each measurement. The Wenner-Schlumberger array is one of the configurations that can be used for 2D geoelectric survey. This configuration was chosen because it has a horizontal data coverage and penetration depth is quite good. To determine the true resistivity value, the data processing is done using software Res2dinv. The results obtained in the form of the resistivity distribution in the form of 2D contours that indicate subsurface cavities in the line of measurements.